Financial markets - Jörg Bibow (Levy Economics Institute of Bard College, 2011)
This paper provides a brief exposition of financial markets in Post Keynesian economics. Inspired by John Maynard Keynes's path-breaking insights into the role of liquidity and finance in monetary production economies Post Keynesian economics offers a refreshing alternative to mainstream (mis)conceptions in this area. We highlight the importance of liquidity - as provided by the financial system - to the proper functioning of real world economies under fundamental uncertainty, contrasting starkly with the fictitious modeling world of neo-Walrasian exchange economies. The mainstream vision of well-behaved financial markets, channeling saving flows from savers to investors while anchored by fundamentals, complements a notion of money as an arbitrary numéraire and mere convenience, facilitating exchange but otherwise neutral. From a Post Keynesian perspective, money and finance are nonneutral but condition and shape real economic performance. It takes public policy to anchor asset prices and secure financial stability, with the central bank as the key public policy tool.
Keywords: A33; B31; E44; E50; 330; financial markets; liquidity; uncertainty; rate of interest; instability; central banking; Finanzmarkt; Liquiditätspräferenz; Kapitalmarkttheorie; Postkeynesianismus; Theorie